A Retrospective Study of Acute Kidney Injury in Cats and Development of a Novel Clinical Scoring System for Predicting Outcome for Cats Managed by Hemodialysis. (16th May 2013) - Segev, G.; Nivy, R.; Kass, P.H.; Cowgill, L.D.
<x xml:space="preserve">Abstract</x> Background Information regarding acute kidney injury (AKI) in cats is limited, and there are no reliable tools to objectively assess disease severity and predict outcome. Objectives To assess clinical signs, clinicopathologic abnormalities, etiology, and outcome of cats with AKI, and to develop models using clinical metrics and empirically derived scores to predict outcome. Animals One hundred and thirty‐two client‐owned cats. Methods Retrospective study. Bivariate logistic regression analyses were performed to identify variables predictive of 30‐day survival. Continuous variables outside the reference range were divided into quartiles to yield quartile‐specific odds ratios (OR) for survival. Models were developed incorporating weighting factors assigned to each quartile based on the OR. A predictive score for each model was calculated for each cat by summing all weighting factors. A second, multivariable logistic regression model was created from actual values of the same variables. Receiver operating characteristic curve analyses were performed to determine the models' performance. Models were further tested using a subset of cases not used in initial assessment. Results Fifty five of 132 cats (42%) remained dialysis‐independent for at least 30 days after discharge, and the remaining 77 cats either died (n = 37, 28%) or were euthanized (n = 40, 30%). The most common etiology was ureteral obstruction (n = 46, 35%). Higher scores were associated with decreased probability of survival (P < .001). Models correctly classified outcomes in 75–77% of the cases and 84–89% of the cases in the subsequent evaluation. Conclusions and Clinical Importance Models can provide objective guidance in assessing AKI prognosis and severity, but should be validated in other cohorts of cats.